Molecular detection and characterization of infectious bronchitis virus in live bird markets in Jos, Plateau State, Nigeria - Bitrus Inuwa; Hassan I. Musa; Hanbali I. Umar; Abdulyekin O. Tijani; Shuaibu G. Adamu; Muhammed A. Sodiq; Ismaila Shittu; Clement Meseko; Tony Joannis (The Proceedings of the Nigerian Academy of Science)
Infectious Bronchitis Virus (IBV) is a highly contagious coronavirus of chickens, ducks, turkeys and Pheasants. It mostly affects the respiratory, urinary and reproductive tracts, leading to considerable economic losses in the poultry industry as a result of drop in egg production, undesirable egg quality and poor weight gain. Thus, this study was designed to detect and characterize IBV circulating in live bird markets (LBMs) in Plateau State, Nigeria. One hundred pools of tracheal and cloacal swabs each were collected from two LBMs in Jos. Viral RNA was extracted and screened for IBV using real-time RT-PCR. Subsequently, the hypervariable region of the spike (S1) gene of positive samples was amplified and sequenced. The IBV nucleic acid was detected in 42% (42/100) of the pooled samples. Phylogenetic analysis of the S1 gene sequences showed that the IBV detected in this study belonged to two distinct genotypes: GI-14, and GI-23, with three clustering within the GI-23 group. One isolate showed a notable relationship with a previously reported Nigerian isolate, sharing 85% nucleotide identity, and formed a cluster within the GI-14 group. Overall, this study established IBV spread and therefore we recommend continuous surveillance to identify the current circulating strain for possible local vaccine development for effective control measures to mitigate the spread of the virus in the study area and the country at large.